Feline Injection-Site Sarcoma: Matrix Remodeling and Prognosis. (March 2017) - Porcellato, I.; Menchetti, L.; Brachelente, C.; Sforna, M.; Reginato, A.; Lepri, E.; Mechelli, L.
Feline injection-site sarcoma (FISS) is an aggressive tumor believed to arise from the proliferation of fibroblasts and myofibroblasts in areas of chronic inflammation, particularly at sites of injection. Local recurrence is frequent after surgical excision. Gelatinases (MMP-2 and MMP-9) and their inhibitor (TIMP-2) are endopeptidases pivotal in extracellular matrix remodeling and therefore in tumor invasiveness. The aim of this study was to investigate the immunohistochemical expression of MMP-2, MMP-9, and TIMP-2 in FISS to assess their usefulness as prognostic factors. Size, soft tissue sarcoma (STS) grading system, depth of infiltration, surgical margins, and Ki-67 index were evaluated as additional prognostic markers. Twenty-four cases of primary FISS were classified according to clinical follow-up as nonrecurrent (NR, n = 14; 58.3%) and recurrent (R, n = 10; 41.7%). MMP-2, MMP-9, and TIMP-2 were variably expressed in the FISS examined, confirming their role in tumor invasiveness, yet they did not show significant differences between the R and NR groups. These results could be due to different tumor stages or to the multiple activities of these enzymes, not limited to ECM remodeling. The immunohistochemical expression of these enzymes considered alone does not seem to be useful as a prognostic marker. STS grading system, depth of infiltration, surgical margins, and Ki-67 index did not relate to recurrence. Instead, the size of the tumor, measured after formalin fixation, with an optimal cutoff of 3.75 cm (accuracy = 86%; P < .05), and the mitotic count, with an optimal cutoff of 20 mitoses/10 HPF (accuracy = 80%; P < .05), could be evaluated as useful prognostic markers.